2009
DOI: 10.3923/pjbs.2009.433.438
|View full text |Cite
|
Sign up to set email alerts
|

Combining Ability and Heterosis for Some Agronomic Traits in Crosses of Maize

Abstract: In 2007, five maize inbred lines were crossed in all possible combinations without reciprocals by using a half diallel crosses mating design to obtain 10 single cross. Inbred parents and their F1 single crosses were evaluated through 2008 season to evaluate the role of general and specific combining ability and heterosis for some agronomic traits. Results indicated that mean squares of genotypes were highly significant for all studied traits, i.e., ear diameter, ear length, number of kernels/row, 100-kernel we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
12
3
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 3 publications
11
12
3
4
Order By: Relevance
“…It indicated that all but above mentioned two traits were governed by both additive and non-additive gene action. Similar findings in maize were reported by Aguiar et al (2004), Bhatnagar et al (2004) and Abdel-Moneam et al (2009). The additive gene action played a major role in controlling the character days to tasseling and days to maturity because of non-significant SCA of these characters.…”
Section: Analysis Of Variancesupporting
confidence: 83%
“…It indicated that all but above mentioned two traits were governed by both additive and non-additive gene action. Similar findings in maize were reported by Aguiar et al (2004), Bhatnagar et al (2004) and Abdel-Moneam et al (2009). The additive gene action played a major role in controlling the character days to tasseling and days to maturity because of non-significant SCA of these characters.…”
Section: Analysis Of Variancesupporting
confidence: 83%
“…Predominance of additive gene action for various quantitative traits in maize was reported by Muraya et al (2006), Ahmed et al (2008) and Amiruzzaman (2010). The current result was in contrast with Abdel-Moneam et al (2009) who observed GCA/SCA ratio was less than unity for 100-kernels weight and ear yield/plant indicating non additive gene action in controlling the traits. Kadir (2010) in his study showed that the non-additive effects (SCA) were more important than additive effects (GCA) for plant height, ear height, days to pollen shedding, days to silking, 1000-seed weight and grain yield/plant.…”
Section: Resultscontrasting
confidence: 56%
“…Ragam DGU dan DGK yang nyata memberikan indikasi bahwa baik gen aditif maupun non-aditif memberikan pengaruh nyata pada karakter yang diamati. Hasil ini sesuai dengan yang ditemukan oleh Abdel-Moneam et al (2009);Zivanovic et al (2010); Bocanski et al (2010) dan El-Badawy (2012) dimana DGU dan DGK berpengaruh nyata pada karakter hasil biji, panjang tongkol, diameter tongkol, jumlah baris biji, rendemen dan bobot 1,000 biji. Penelitian Iriany et al (2011), DGU dan DGK berpengaruh nyata pada hasil biji dan diameter tongkol.…”
Section: Daya Gabung Umumunclassified
“…Nilai DGK positif menunjukkan bahwa tetua tersebut mempunyai kombinasi hibrida yang tinggi dengan salah satu tetua yang digunakan. Nilai DGK pada karakter hasil biji dan diameter tongkol menunjukkan nilai positif, hal tersebut sejalan dengan penelitian Abdel-Moneam et al (2009), Zivanovic et al (2010 dan Yustiana et al (2013). Nilai DGK yang tinggi pada hasil biji dan diameter tongkol juga dilaporkan oleh Iriany et al (2011) kedua grup penyusunnya.…”
Section: Daya Gabung Khususunclassified
See 1 more Smart Citation